Dynamics of semigroups generated by analytic functions of the Laplacian on Homogeneous Trees - Kumar, Pratyoosh; Rano, Sumit Kumar (Comptes Rendus. Mathématique)
Let $Ψ $ be a non-constant complex-valued analytic function defined on a connected, open set containing the $L^p$-spectrum of the Laplacian $\mathcal{L}$ on a homogeneous tree. In this paper we give a necessary and sufficient condition for the semigroup $T(t)=e^{tΨ (\mathcal{L})}$ to be chaotic on $L^{p}$-spaces. We also study the chaotic dynamics of the semigroup $T(t)=e^{t(a\mathcal{L}+b)}$ separately and obtain a sharp range of $b$ for which $T(t)$ is chaotic on $L^{p}$-spaces. It includes some of the important semigroups such as the heat semigroup and the Schrödinger semigroup.